2005
DOI: 10.1007/s10453-005-4180-1
|View full text |Cite
|
Sign up to set email alerts
|

Long term trends in outdoor Aspergillus/Penicillium spore concentrations in Derby, UK from 1970 to 2003 and a comparative study in 1994 and 1996 with the indoor air of two local houses

Abstract: Aspergillus/Penicillium spore concentrations have been monitored in Derby since 1970 using a volumetric spore trap, with full year data from 1991. In addition a short comparative study with the indoor air was undertaken at two local houses in 1994 and 1996. Aspergillus/Penicillium spores were present in the Derby air throughout the year and often reached maximum monthly cumulative concentrations in the autumn, although they were occasionally the dominant spores in the winter when total spore concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 22 publications
4
19
1
Order By: Relevance
“…Contrasting results were obtained in previous work which reported that the highest Aspergillus/Penicillium hourly spore concentration occurred at 10.00 h, decreased after 14.00 h, and remained lower for the rest of the day (Gillum and Levetin 2008). Likewise, in Derby (UK), on peak days, the highest Aspergillus/ Penicillium spore concentrations usually occurred towards the middle of the day, around 11.00 h (Millington and Corden 2005).…”
Section: Previous Work Reported Similar Results-increases Incontrasting
confidence: 81%
“…Contrasting results were obtained in previous work which reported that the highest Aspergillus/Penicillium hourly spore concentration occurred at 10.00 h, decreased after 14.00 h, and remained lower for the rest of the day (Gillum and Levetin 2008). Likewise, in Derby (UK), on peak days, the highest Aspergillus/ Penicillium spore concentrations usually occurred towards the middle of the day, around 11.00 h (Millington and Corden 2005).…”
Section: Previous Work Reported Similar Results-increases Incontrasting
confidence: 81%
“…For example, while Li and Kendrick (1995) did not find intradiurnal patterns, Millington and Corden (2005), similarly to our study, detected an increase in the concentrations of Aspergillus/Penicillium spores outdoors at around 11:00 hours. However, this behaviour is altered in the case of interior environments, where increases in the spore levels are directly associated with the activities carried out in these spaces.…”
Section: Discussionsupporting
confidence: 80%
“…Only Corden et al (2003) displayed region-specific trends of a single fungal species and for the period 1970e1996. However, a follow-up study on Aspergillus/Penicillium spore concentrations (Millington and Corden, 2005) revealed no trend for the period 1970e2003; spores from these fungal genera are not included among those contributing 0.1 % in the air of Thessaloniki. To our knowledge, there is no study dealing with long-term trends in airborne spore levels for a wide range of fungal taxa and, hence, there is no information to compare our results with.…”
Section: Discussionmentioning
confidence: 91%